Pengaruh Kompetensi Guru dan Kompensasi terhadap Kinerja Guru Sekolah Dasar Negeri di Wilayah Kecamatan Sukajadi - Lutfia Nurhalisa Vinakesti (UNISBA Press, 2022)
Abstract. The purpose of this research is 1) To find out how Teacher Competence and Compensation are for public elementary school teacher in the Sukajadi District, 2) To find out how the performance of state elementary school teachers in the Sukajadi District area, 3) To analyze how the influence of Teacher Competence and Compensation on Teacher Performance public elementary school in Sukajadi District. The methods of this research is descriptive and verification analysis and it was calculated by using SPSS 25.0 program. Methods of collecting data obtained through observation and questionnaires. Respondents in this study were public elementary schools teachers totaling 84 people. Sampling technique is the Isaac and Michael formula and the Disproportionate Stratified Random Sampling technique. The independent variabels studied in this study were Teacher Competence (X1) and Compensation (X2), while the dependent variable was Teacher Performance (Y). The results of this study conclude that :1) The competence of stte elementary school teacers in the Sukajadi District area is included the sufficent category. 2) Compensation in public elementary schools in the Sukajadi sub-district is included in the sufficent category. 3) Teacher performance of state elementary schools in the Sukajadi sub-district is included in the sufficent category. 4) Teacher competence partially has a positive and significant effect on teacher performance. 5) Compensation partially has a positive and significant effects on teacher performance. 6) Teacher Competence and Compensation simultaneously have a positive and significant effect on teacher performance in public elementary schools in the Sukajadi District. It can be concluded that there is an influence between Teacher Competence and Compensation on the Performance of State Elementary School Teachers in the Sukajadi District. Abstrak. Penelitian ini bertujuan 1) Untuk mengetahui bagaimana Kompetensi Guru dan Kompensasi pada guru sekolah dasar negeri di wilayah Kecamatan Sukajadi, 2) Untuk mengetahui bagaimana Kinerja Guru sekolah dasar negeri di wilayah Kecamatan Sukajadi, 3) Untuk menganalisis bagaimaa pengaruh Kompetensi Guru dan Kompensasi terhadap Kinerja Guru sekolah dasar negeri di wilayah Kecamatan Sukajadi. Metode pengumpulan data yang diperoleh melalui observasi dan kuesioner. Responden dalam penelitian ini adalah guru sekolah dasar negeri di wilayah Kecamatan Skajadi berjumlah 84 orang guru. Teknik pengambilan sampel dengan rumus Isaac dan Micahel dan teknik Dispropotionate Stratiefied Random Sampling. Variabel bebas yang dikaji dalam penelitian ini adalah Kompetensi Guru (X1) dan Kompensasi (X2), sedangkan variabel terkaitnya adalah Kinerja Guru (Y). Hasil penelitian ini menyimpulkan bahwa : 1) Kompetensi Guru sekolah dasar negeri di wilayah Kecamatan Sukajadi termasuk pada kategori cukup. 2) Kompensasi di sekolah dasar negeri di wilayah Kecamatan Sukajadi temasuk pada kategori cukup. 3) Kinerja Guru sekolah dasar negeri di wilayah Kecamatan Sukajadi termasuk ada kategori cukup. 4) Kompetensi Guru secara parsial berpengaruh positif dan signifikan terhadap Kinerja Guru, 5) Kompensasi secara parsial berpengaruh positif dan signifikan terhadap Kinerja Guru, 6) Kompetensi Guru dan Kompensasi secara simultan berpengaruh positif dan signifikan terhadap Kinerja Guru sekolah dasar negeri di wilayah Kecamatan Sukajadi. Dapat disimpulkan bahwa terdapat pengaruh antara Kompetensi Guru dan Kompensasi terhadap Kinerja Guru Sekolah Dasar Negeri di wilayah Kecamatan Sukajadi.